(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
The strain rate sensitivity of Oxygen plasma treated Nano Silicon Dioxide particles sol-gel coated Vectran and concurrent microstructural evolution was investigated. Both the materials are strain rate sensitive and the change in index parameter of strain rate sensitivity with strain reflects the change in micromechanisms of deformation and modes of fracture. Helium plasma can reduce the surface energy of vectran fiber. Oxygen plasma and nano SiO2 particles will enhance the surface energy. The activation volumes rise with Oxygen. Although either Helium or Oxygen has made the activation volumes exceed that of the neat Vectran, the SiO2 nano-particle makes the activation volume rise rapidly.